Self-Esteem Pada Guru Taman Kanak-Kanak (TK) - Anis Fitria; Della Nur Shayidah; Putri Wulansari; Rini Mutianisa; Viona Rahmawati Jubaidah; Viony Rahmawati Jubaidah (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research aims to explore and understand self-esteem among Kindergarten (TK).TK teacher is responsible for a child's basic abilities in the field of education, not only teaching educational concepts but also introducing children to behaviors and daily life. The research subjects are TK teachers, and the study adopts a qualitative method with a descriptive approach. Qualitative research emphasizes natural or intrinsic processes, prioritizing meanings that are not tested or measured precisely with descriptive data. The study describes incidents heard, felt, and formulated in narrative or descriptive statements. This research is characterized by its naturalistic setting, focusing on the quality of phenomena. The results indicate that the depiction of self-esteem among TK teachers in various regions/schools can be concluded based on the overall observed participants. The findings suggest that teacher creativity can be enhanced to influence teaching quality, and there is a significant positive relationship between communication skills components and teacher work effectiveness. In conclusion, TK teachers exhibit good levels of self-esteem, as most fall into the "Good" category based on data analysis. The self-esteem of TK teachers positively and significantly influences students' social aspects.